Association between ultra-processed food intake and risk of colorectal cancer: a systematic review and meta-analysis - Shu, Long; Huang, Yiqian; Si, Caijuan; Zhu, Qin; Zheng, Peifen; Zhang, Xiaoyan (Frontiers in Nutrition, 2023)
Background: Although some epidemiological studies have shown a positive relationship between high intake of ultra-processed food(UPF) and risk of colorectal cancer(CRC), the results remain inconsistent. Therefore, we conducted this systematic review and meta-analysis to clarify the association between UPF intake and CRC risk. Methods: PubMed/MEDLINE, Web of Science, EMBASE, China National Knowledge Infrastructure (CNKI) and Wan fang databases were used to search the relevant studies published up to February 2023. The summary relative risks(RRs) with the corresponding 95% confidence intervals(CIs) were estimated by comparing the highest category versus the lowest category of UPF intake, using the random-effects models(DerSimonian-Laird method). Heterogeneity between studies was explored using the Cochran’s Q test and I-square(I2). Publication bias was assessed by examining the funnel plots, and quantified by Begg’s or Egger’s tests. Results: A total of seven articles(three cohort and four case-control studies), involving 18673 CRC cases and 462292 participants, were included in our study. Combining nine effect sizes from seven articles, an increased risk of CRC was shown in the highest compared with the lowest category of UPF intake(RR=1.26;95%CI:1.14-1.38,P<0.0001). Subgroup analyses showed a positive association between UPF intake and CRC risk in case-control studies(RR=1.41; 95%CI: 1.22-1.63, P<0.0001). When we conducted analyses separately by study area, there was a significant association between UPF intake and CRC risk in developed countries(RR=1.20; 95%CI: 1.11-1.30, P<0.0001). Conclusions:Our results show that high UPF intake is significantly associated with a higher risk of CRC, in the absence, however, of a dose-response association. Further studies in particular of large prospective cohort studies are necessary to confirm these results.